Production potential of adzuki bean (Vigna angularis) lines in three localities in Costa Rica. - Araya, Rodolfo; Valerio, Eddy; Hernández, Hugo (Agronomía Mesoamericana, 2016)
Between 1984 and 1988, fourteen adzuki bean lines were evaluated in three localities in Costa Rica: Alajuela at 840 masl., Perez Zeledon at 760 masl. and Rio Frio at 100 masl. Three common bean varieties were used as controls: Talamanca, Huetar and Mexico 80. The best adzuki lines in the three localities were U CR - 2 and U CR - 7 (red colored grain) and UCR-3 (black colored grain). In Rio Frio and Perez Zeledon, the adzuki showed a like production as the common bean, due to the low incidence of Web blight (Thanatephorus cucumeris Frank Donk). This is a fungus which slightly affects the adzuki bean, but it is a limiting factor for common bean production in these two localities. In Alajuela, an ideal zone for common bean production, several adzuki lines showed a higher productivity.